(untitled) (Ameghiniana, 2013)
The three new fossil taxa here described are: Rhapsodus tedfordi gen. et sp. nov., from the Lower Snake Creek Formation (Barstovian) of Nebraska, is the most primitive form of the Procyoninae and the closest to the Bassariscinae lineage. Protoprocyon savage gen. et sp. nov., from the Ash Hollow Formation (late Clarendonian to early Hemphillian) of Nebraska, is a transitional form between Rhapsodus and the following Cyonasua. Finally Cyonasua pascuali sp. nov., from the Huayquerias Formation (Huayquerian) of Mendoza, Argentina, is a small and primitive species related to Protoprocyon savagei. Cyonasua pascuali probably was the oldest representative of the Order Carnivora in South America. The presence of juvenile, unidentifiable, remains, in levels of probably the same age in Catamarca appear to confirm this conclusion. The Late Miocene age of these levels ratifies that the great American faunal interchange was an event prior to the Pliocene. The close affinities between P. savagei and C. pascuali, also suggest the correlation between the mammal-ages Hemphillian and Huayquerian.